Control of respiratory and cardiovascular functions by leptin - Bassi, M. [UNESP]; Furuya, Werner I. [UNESP]; Zoccal, D. B. [UNESP]; Menani, Jose Vanderlei [UNESP]; Colombari, E. [UNESP]; Hall, J. E.; Silva, A. A. da; Carmo, Jussara Márcia do; Colombari, D. S. A. [UNESP] (Elsevier, 2015)
Leptin, a peptide hormone produced by adipose tissue, acts in brain centers that control critical physiological functions such as metabolism, breathing and cardiovascular regulation. The importance of leptin for respiratory control is evident by the fact that leptin deficient mice exhibit impaired ventilatory responses to carbon dioxide (CO2), which can be corrected by intracerebroventricular leptin replacement therapy. Leptin is also recognized as an important link between obesity and hypertension. Humans and animal models lacking either leptin or functional leptin receptors exhibit many characteristics of the metabolic syndrome, including hyperinsulinemia, insulin resistance, hyperglycemia, dyslipidemia and visceral adiposity, but do not exhibit increased sympathetic nerve activity (SNA) and have normal to lower blood pressure (BP) compared to lean controls. Even though previous studies have extensively focused on the brain sites and intracellular signaling pathways involved in leptin effects on food intake and energy balance, the mechanisms that mediate the actions of leptin on breathing and cardiovascular function are only beginning to be elucidated. This mini-review summarizes recent advances on the effects of leptin on cardiovascular and respiratory control with emphasis on the neural control of respiratory function and autonomic activity.
Keywords: Obesity; Leptin; Chemoreflex; Sympathetic nerve activity; Breathing; Blood pressure